THE DEVELOPMENT OF C1 CUBIC TIMMER TRIANGULAR PATCHES FOR SCATTERED DATA INTERPOLATION - MOHD ALI, FATIN AMANI (2020)
This study discusses the construction of a cubic Timmer triangular patch defined on a triangular domain. Cubic Timmer basis function has its advantages compared with cubic Ball and cubic Bézier bases. Notably, it will interpolate the midpoint of control polygon. The construction of the cubic Timmer triangular patch is based on the main idea from cubic Ball and cubic Bézier triangular patches. Some properties of the cubic Timmer triangular patch are investigated in detail. Finally, the cubic Timmer triangular patch is used to reconstruct a surface from non-uniform and uniform scattered data. To do this, we employ three stages algorithm